GOOD CORPORATE GOVERNANCE, UKURAN PERUSAHAAN DAN KONSERVATISME AKUNTANSI TERHADAP FINANCIAL DISTRESS PADA PERUSAHAAN SEKTOR TRANSPORTASI DAN LOGISTIK YANG TERCATAT DI BEI PERIODE 2017-2021 - Hari Pamungkas (ICMA Nasional, 2023)
Financial distress is a stage in which a company’s financial condition may eventually lead to bankruptcy. The recent Covid-19 Pandemic, with its economic impact hitting hard on company's ability to strive financially. The bad implementation of GCG seems to be one of the major factor that causes such a repercussion. The study aims to determine the effect of good corporate governance, firm size, and accounting conservatism on financial distress. The sample in this study amount to 12 companies in the transportation and logistics sector listed on the Indonesian Stock Exchange for the 2017-2021 period. The method used in this research is descriptive quantitative method. The data analysis technique used is multiple linear regression analysis technique. The result show that the independent commissioners has a partial effect on financial distress as evidenced by a significance value of 2.3%. While the good corporate governance variable as measured by institutional ownership, managerial ownership, audit committee, firm size measured by the natural logarithm of total assets, and the accounting conservatism measured by accrual model does not partially affect on financial distress as indicated by a value greater than 5%. The results of the f test show that institutional ownership, managerial ownership, independent commissioners, audit committees, firm size and accounting conservatism have a simultaneous effect on financial distress as evidenced by a significance value of 1%. While the results of the coefficient of determination or R2 in this study were 28.6%.